Efecto de Solanum sessiliflorum dunal sobre el metabolismo lipídico y de la glucosa - Pardo S., María A. (2004)
It was studied the effect of Cocona extract in glucose, cholesterol, LDL-c, HDL-c, triglycerides, in100 subjects with dislipemia and hyperglycemia When Determining the baseline concentrations of the parameters in this study, it was adminiridosed to the patients 40 mL /day of Cocona extract  during 3 days The mathematical /statistical study of the obtained results permitted to establish that the decays of serum blood cholesterol, LDL-c, triglycerides and glucose, are statistically significant ( p<0.05 ). Cholesterol reached nornal values in the 61% of the subject; LDLc in the 62 %; triglycerides in the 92% it was observed a significant increase of HDL--c in the 82%. As well as, it is important to sign that, in terms of normal baseline glycemia of some of the nornal subjects, in no one of the cases, it was developed hypoglycaemia after the treatment with cocona.